What Is Metaverse?—A Definition Based on Qualitative Meta-Synthesis - Weinberger, Markus (Future internet, 2022)
The term Metaverse has received much attention in various industries, in society, and, increasingly, in scientific communities. This creates demand for a comprehensive and broadly accepted definition of the subject, which is well grounded in research. At the same time, the Metaverse is rather a vision under evolution than an examinable phenomenon. Therefore, this study applied an adapted version of the meta-synthesis method to analyze the existing literature and distill a proposal for a Metaverse definition. The adapted method takes the nature of the subject into account by weighing younger publications with many citations over older, less influential documents. Initially, 47 publications were fed into the process, of which 24 were left after the primary analysis. As a result of the analysis, the following definition is proposed: “The Metaverse is an interconnected web of ubiquitous virtual worlds partly overlapping with and enhancing the physical world. These virtual worlds enable users represented by avatars to connect and interact with each other, to experience and consume user-generated content in an immersive, scalable, synchronous and persistent environment. An economic system provides incentives for contributing to the Metaverse.” The meta-synthesis method ensures a systematic and reproducible approach while at the same time preserving the original voice and notion of the analyzed literature in order to create new knowledge based on the existing literature; thus the proposed Metaverse definition might serve as a helpful foundation for future research.